No significant benefit of moderate-dose vitamin C on severe COVID-19 cases - Zheng Shaoping (De Gruyter, 2021)
There is no specific drug for coronavirus disease 2019 (COVID-19). We aimed to investigate the possible clinical efficacy of moderate-dose vitamin C infusion among inpatients with severe COVID-19. Data of 397 adult patients with severe COVID-19 admitted to a designated clinical center of Wuhan Union Hospital (China) between February 13 and February 29, 2020, were collected. Besides standard therapies, patients were treated with vitamin C (2–4 g/day) or not. The primary outcome was all-cause death. Secondary outcome was clinical improvement of 2 points on a 6-point ordinal scale. About 70 participants were treated with intravenous vitamin C, and 327 did not receive it. No significant association was found between vitamin C use and death on inverse probability treatment weighting (IPTW) analysis (weighted hazard ratio [HR], 2.69; 95% confidence interval [CI], 0.91–7.89). Clinical improvement occurred in 74.3% (52/70) of patients in the vitamin C group and 95.1% (311/327) in the no vitamin C group. No significant difference was observed between the two groups on IPTW analysis (weighted HR, 0.76; 95% CI, 0.55–1.07). Our findings revealed that in patients with severe COVID-19, treatment with moderate dose of intravenous vitamin C had no significant benefit on reducing the risk of death and obtaining clinical improvement.